The Effect of Coal Characteristics on Adsorption and Desorption Gas at Indonesia Low Rank Coal - Ogara, Evan Rosyadi (2017)
Enhanced coalbed methane (ECBM) is the common application of carbon capture storage (CCS) which has advantages: (1) capture and storage of carbon dioxide (CO2) for long term, (2) increase methane (CH4) production. This study reports the effect of coal characteristics on sorption capacity at low rank coal in Indonesia and measuring CH4 displacement by CO2/N2 injection. The coal samples are from Muara Enim, Warukin and Balikpapan Formation with low rank coal. The influence of coal characteristics on sorption capacity and desorption estimated by combining proximate analysis with sorption analysis in histogram and curve. Adsorption measurement were carried out at 23ºC with pressure around 5 MPa for CO2 and 4 MPa for CH4. Desorption experiment, N2 is injected to reference coal saturated with CH4 while, another desorption CO2 is injected to the same coal sample after vacuumed first then resaturated with CH4. All of experiment were performed on powdered coal (<1/256 mm) and wet condition. The ratios of the final sorption capacities of CH4 between 0.10 – 0.16 mmol/gr. Warukin Formation has the highest sorption for CH4 followed by Balikpapan and Muara Enim. The sorption capacities of CO2 vary between 1.25-1.43 mmol/gr, Balikpapan Formation has the highest sorption for CO2 followed by Muara Enim and Warukin. The recovery factor of CH4 vary between 5-13% for N2 injection and 20-46% for CO2 injection.